2002
DOI: 10.1191/0969733002ne539oa
|View full text |Cite
|
Sign up to set email alerts
|

A Fundamental Ethical Approach to Nursing: some proposals for ethics education

Abstract: The purpose of this article is to explore a fundamental ethical approach to nursing and to suggest some proposals, based on this approach, for nursing ethics education. The major point is that the kind of nursing ethics education that is given reflects the theory that is held of nursing. Three components of a fundamental ethical view on nursing are analysed more deeply: (1) nursing considered as moral practice; (2) the intersubjective character of nursing; and (3) moral perception. It is argued that the fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 26 publications
4
95
0
5
Order By: Relevance
“…Integrating ethical codes more fully into professional training is seen as one way of managing the tension between over-vague principles and over-instructive diktats (Gastman, 2002). In an American study, Masters of Social Work (MSW) students indicated that they did not feel adequately prepared to handle sexual feelings towards or from a service user (Berkman et al, 2000).…”
Section: Recognition and Reportingmentioning
confidence: 99%
“…Integrating ethical codes more fully into professional training is seen as one way of managing the tension between over-vague principles and over-instructive diktats (Gastman, 2002). In an American study, Masters of Social Work (MSW) students indicated that they did not feel adequately prepared to handle sexual feelings towards or from a service user (Berkman et al, 2000).…”
Section: Recognition and Reportingmentioning
confidence: 99%
“…MacIntyre (1984) claimed that a practice involves internal good which is realized through the activities of that practice. The internal good of nursing practice is reflected in the overarching goal: to ensure the well-being of the infirm (Gastmans, 2002). This assumes having an insight into and an understanding of what is good or bad, harmful or comforting for patients (Scott, 2006), as well as having the capability to meet those demands.…”
Section: Introductionmentioning
confidence: 98%
“…It has been generally accepted that nurses are confronted with unique ethical problems that arise from their participation in patient care (4). Ethical knowledge helps professionals justify what is or is not correct and appropriate professional conduct.…”
Section: Introductionmentioning
confidence: 99%